(untitled) (Iranian Journal of Kidney Diseases, 2012)
Kidney transplantation has been established as the treatment of end-stage renal disease. Despite great improvement in transplant science, complications are still frequently seen after kidney transplantation. We describe the first case of isolated angiomyolipoma in the kidney allograft developed 3 years after transplantation and treated with partial nephrectomy of the allograft.